EFFECTIVE STRATEGIES FOR ENHANCING THE PROFESSIONAL-GNOSTIC COMPETENCY OF ASPIRING FOREIGN LANGUAGE TEACHERS (Multidisciplinary Journal of Science and Technology, 2024)
The article discusses a number of technologies that contribute to students' professional competence development, including independent educational activity, which determines a future language teacher's ability to practically reorganize their own activities, resulting in an interlingual and intercultural language personality. The article examines a number of technologies that contribute to the development of students' professional competence, including independent educational activity, which determines a future foreign language teacher's ability to practically reorganize their own activities, resulting in an interlingual and intercultural language personality.